Nitrate Supplementation Combined with a Running Training Program Improved Time-Trial Performance in Recreationally Trained Runners - Jeferson Santana; Diana Madureira; Elias de França; Fabricio Rossi; Bruno Rodrigues; André Fukushima; François Billaut; Fabio Lira; Erico Caperuto (MDPI AG, 2019)
Our purpose was to verify the effects of inorganic nitrate combined to a short training program on 10-km running time-trial (TT) performance, maximum and average power on a Wingate test, and lactate concentration ([La−]) in recreational runners. Sixteen healthy participants were divided randomly into two groups: Nitrate (n = 8) and placebo (n = 8). The experimental group ingested 750 mg/day (~12 mmol) of nitrate plus 5 g of resistant starch, and the control group ingested 6 g of resistant starch, for 30 days. All variables were assessed at baseline and weekly over 30 days. Training took place 3x/week. The time on a 10-km TT decreased significantly (p < 0.001) in all timepoints compared to baseline in both groups, but only the nitrate group was faster in week 2 compared to 1. There was a significant group × time interaction (p < 0.001) with lower [La] in the nitrate group at week 2 (p = 0.032), week 3 (p = 0.002), and week 4 (p = 0.003). There was a significant group time interaction (p = 0.028) for Wingate average power and a main effect of time for maximum power (p < 0.001) and [La−] for the 60-s Wingate test. In conclusion, nitrate ingestion during a four-week running program improved 10-km TT performance and kept blood [La−] steady when compared to placebo in recreational runners.